Moderate-to-late prematurity: understanding respiratory consequences and modifiable risk factors - Kishan D. Tsang; Gerdien A. Tramper-Stranders; Jasper V. Been; Angelique K. Hoffmann-Haringsma; Irwin K. Reiss; Marielle W.H. Pijnenburg; Ismé M. De Kleer (European Respiratory Review)
As survival rates of preterm infants have increased due to advances in perinatal care, focus has shifted towards the profound long-term effects of prematurity. An extensive amount of evidence has shown increased susceptibility to chronic illnesses among preterm infants. While the onset of such conditions typically emerges during adulthood, their roots trace back to the early stages of life. Much of this interest has been directed towards short- and long-term consequences of extreme and very preterm birth. However, it has become apparent that, despite a limited risk of complications during the neonatal period, the moderate and late preterm population suffers from an increased likelihood of morbidity during the course of life. Considering the higher prevalence of moderate and late preterm births compared to extreme and very preterm births, understanding and investigating their health outcomes is essential to address the broader impact of prematurity. In this review, we will discuss the impact of moderate and late prematurity on lung development, function and how environmental factors impose these individuals to increased risk for respiratory morbidity during the course of life. We describe interventions during early life that may protect the moderate-to-late preterm population from adverse lung development and further deterioration by addressing modifiable risk factors.